2015
DOI: 10.4014/mbl.1501.01003
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Enzymatic Hydrolysate from Sargassum thunbergii Using Vibrio crassostreae PKA 1002 Crude Enzyme

Abstract: An alginate degrading enzyme from the Vibrio crassostreae PKA 1002 strain was used to hydrolyze the water extract of Sargassum thunbergii. To obtain the optimum degrading conditions for the S. thunbergii water extract, the mixture of the water extract and enzyme was incubated at 30 o C for 0, 3, 6, 12, and 24 h, and its alginate degrading ability was measured by reducing sugar and viscosity. A temperature of 30 o C for a period of 6 h was found to be the optimal condition for the enhancement of the alginate's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…As a result, with increasing incubation time, the value of redness (a*) increased, and it was measured as 10.27 at 6 h, which then gradually decreased to 8.27 for 24 h. In the case of yellowness (b*), the highest value was 63.95 at 3 h. The lightness (L *) decreased with increasing incubation time and gradually tended to darken. The lowest value at 12 h was measured as 39.84, and thereafter, it increased continuously to 44.96 at 48 h. This result is in accordance with the results of Bark et al [3], which reported that lightness decreased and redness and yellowness were increased by the enzymatic reaction using a crude enzyme.…”
Section: Results and Discussion Ph And Chromaticity Of Upt Enzymatic Extractssupporting
confidence: 91%
See 2 more Smart Citations
“…As a result, with increasing incubation time, the value of redness (a*) increased, and it was measured as 10.27 at 6 h, which then gradually decreased to 8.27 for 24 h. In the case of yellowness (b*), the highest value was 63.95 at 3 h. The lightness (L *) decreased with increasing incubation time and gradually tended to darken. The lowest value at 12 h was measured as 39.84, and thereafter, it increased continuously to 44.96 at 48 h. This result is in accordance with the results of Bark et al [3], which reported that lightness decreased and redness and yellowness were increased by the enzymatic reaction using a crude enzyme.…”
Section: Results and Discussion Ph And Chromaticity Of Upt Enzymatic Extractssupporting
confidence: 91%
“…The lowest value at 12 h was measured as 39.84, and thereafter, it increased continuously to 44.96 at 48 h. This result is in accordance with the results of Bark et al . [ 3 ], which reported that lightness decreased and redness and yellowness were increased by the enzymatic reaction using a crude enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, studies have concentrated on the ecology and cultivation of Sargassum thunbergii (Umezaki, 1974). Korean studies of Sargassum thunbergii have examined its physiological (Bark et al, 2015) and antibacterial (Lee et al, 2009) activities, and chlorophyll A isolated from the chloroform fractions. Additional studies have examined the lipase inhibitory activity of the extract (Kim, Kim, and Ahn, 2014), size distribution and growth (Koh, Kim, and Kang, 1993), and effect of sediment on the early life cycle of Sargassum thunbergii (Gao et al, 2019) and morphological changes (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%